Review : Interaksi farmakokinetik dan farmakodinamik metformin-herbal - Ating Cicih; Widhya aligita; Elis susilawati (Universitas Islam Indonesia, 2022)
Background: Diabetes mellitus is a metabolic disorder characterized by hyperglycemia. Metformin is the first-line therapy for type-2 diabetes mellitus. The combination of synthetic drugs with herbs was reported to be superior and popular compared to monotherapy. However, drug-herb interactions can have both beneficial and detrimental effects.Objective: This review aimed to identify the interactions that occur between the antidiabetic drug metformin and herbs.Methods: A literature search was done through ScienceDirect, ResearchGate, Pharmaceutics, and Genes by MDPI databases using the keywords metformin, antidiabetic, herb-drug, interaction, pharmacology, combination, pharmacokinetics, and pharmacodynamics.Results: The combination of metformin and such herbs as Korean ginseng (Panax ginseng), Lonicera japonica, Houttuynia cordata, mulberry (Morus alba), banana (Musa sapientum), Momordica charantia, coconut (Cocos nucifera), and Scutellaria baicalensis showed pharmacokinetic interactions in the form of increasing plasma metformin uptake mediated by MATE1 inhibition and increased OCT1, as well as hOCT2 inhibition which caused decreased metformin uptake in the kidneys. The pharmacodynamic interactions showed a direct effect, both additive and synergistic effects, in reducing blood glucose levels.Conclusion: Consuming metformin with herbs shows the potential for drug interactions in terms of both pharmacokinetics and pharmacodynamics.Keywords: pharmacokinetic, pharmacodynamic, herb-drug, metformin IntisariLatar belakang: Diabetes melitus yaitu gangguan metabolisme yang ditandai dengan hiperglikemia. Metformin merupakan lini pertama pengobatan DM tipe 2. Kombinasi obat sintetis dengan herbal telah dilaporkan menjadi lebih unggul dan populer dibandingkan pengobatan monoterapi saja. Penggunaan obat sintetis dengan herbal dapat memicu interaksi obat yang dapat memberikan efek menguntungkan ataupun merugikan.Tujuan: Review ini bertujuan untuk mengetahui interaksi yang terjadi antara obat antidiabetes metformin dengan herbal.Metode: Penelusuran pustaka melalui database Sciencedirect, Researchgate, Pharmaceutics, dan Genes MDPI dengan penggunaan kata kunci seperti metformin, antidiabetic, herb-drug, interaction, pharmacology, combination, pharmacokinetic, dan pharmacodynamic.Hasil: Kombinasi obat metformin dengan herbal seperti ginseng Korea (Panax ginseng), kamperfuli (Lonicera japonica), amis-amisan (Houttuynia cordata), murbei (Morus alba), pisang (Musa sapientum), pare (Momordica charantia), kelapa (Cocos nucifera), dan kopiah Cina (Scutellaria baicalensis) menunjukkan interaksi farmakokinetik berupa peningkatan penyerapan metformin dalam plasma yang diduga dimediasi oleh penghambatan MATE1 dan peningkatan OCT1, serta penghambatan hOCT2 yang menyebabkan penurunan penyerapan metformin di ginjal. Adapun interaksi farmakodinamiknya menunjukkan efek yang searah baik aditif maupun sinergis dalam penurunan kadar glukosa darah.Kesimpulan: Konsumsi metformin dengan herbal menunjukkan adanya potensi interaksi obat baik secara farmakokinetik ataupun farmakodinamik.Kata kunci: farmakokinetik, farmakodinamik, herbal-obat, metformin